Tipologi dan Potensi Sub Sektor Pertanian di Kabupaten Gianyar - BANI, YOHANES FACRIS; BUDIASA, I WAYAN; WIDYANTARA, I WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
Typology and Potential of Agricultural Sub-Sector in Gianyar Regency The lowest contribution in the formation of GRDP in Gianyar Regency in 2017 by the agricultural category was 12,84 percent (decreased from 13,06 percent in 2016. The purpose of this study was to determine the position of each agricultural sub-sector, base and non-base sub-sectors in the economy in Gianyar Regency Research location was determined deliberately. The research method used the Klassen typology analysis method and Location Quetient with timeseries PDRB data for the last five years (20132017). The results of the Tiplogi comparison were food crop sub-sector, horticulture plant sub-sector annual seasonal plantations and sub-sectors included in the classification of the potency sub-sector or can still develop, while the other agricultural sub-sectors are in the relatively underdeveloped sub-sector classification, the horticulture plant sub-sector a year, annual plantation sub-sector, livestock sub-sector and sub-sector agricultural services and hunting. The results of the location quotient are sub-sectors which are the basic sub-sectors in the economy of Gianyar Regency, namely the food crop sub-sector, annual horticulture sub-sector, and the annual plantation subsector. While the horticultural plant sub sector a year, the annual plantation sub-sector, the livestock sub-sector and the agriculture services and hunting sub-sector are non-base sub-sectors in the economy of Gianyar Regency. The development of agricultural commodities must have strategic characters, such as being oriented to market demand and concentrated on superior products with high competitiveness.